Trade Union Organizations in Vocational-Technical Schools. Between Renewal and Postponement. Chile. 1983-1993 [Organizaciones Sindicales en Liceos Técnicos Profesionales. Entre la Renovación y la Postergación. Chile, 1983-1993] - Alvarez-Vallejos, R; Matamoros-Fernandez, C (Universidad Nacional de Rosario - Facultad de Humanidades y Artes, Escuela de Historia, 2022)
Between 1977 and 1988, the Chilean civic-military dictatorship transferred the administration of 74 vocational-technical schools to groups of national businessmen within educational policies that sought to privatize a large part of the educational system. In these high schools, labor relations dominated by capital were implemented, where workers were forming trade union organizations in the same way as in private companies. In this work we analyze, based on press sources and interviews, the practices and relationships established by these organizations, their conflicts, agreements and political identifications in a historical conjuncture marked by the end of the dictatorship and the arrival of the first civil government, where workers in this sector were left behind from the demands reached in the municipal and private sectors. © 2022 Universidad Nacional de Rosario - Facultad de Humanidades y Artes, Escuela de Historia. All rights reserved.